Analisis Kontribusi Sertifikasi Halal Terhadap Pertumbuhan Industri Catering Di Kota Pekanbaru - Ahmad Ahmad; Mahyarni Mahyarni; Meri Yuliani; Fitrianto Fitrianto; Dian Meliza; Redian Mulyadita (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
Halal certification is a form of government guarantee of the halalness of a product based on Islamic law, which not only serves as a religious marker, but also as a marketing tool and development of the catering industry. This study aims to determine the contribution of halal certification to the growth of the catering industry in Pekanbaru City. This study uses a field research type (Field Research) using a qualitative research approach. The data analysis method used is descriptive qualitative analysis. The results of the study indicate that after obtaining halal certification, there was a significant increase in several business aspects, including increased consumer trust, an increase in the number of orders, expansion of market segments, and increased business turnover. In addition, the certification process also encourages business actors to implement better and more orderly operational standards. Halal certification has been proven to have a positive impact on the growth and professionalism of catering businesses, especially in building the trust of Muslim consumers in Pekanbaru City